Assessment of psychophysical capacities for professional work in late middle age and at the beginning of old age - Agnieszka Ćwirlej-Sozańska; Agnieszka Wiśniowska-Szurlej; Anna Wilmowska-Pietruszyńska; Bernard Sozański; Natalia Wołoszyn (Nofer Institute of Occupational Medicine, 2018)
Background In Poland average life expectancy extends, while the number of the elderly who are active in the labor market decreases. Material and Methods The study population consisted of 429 people aged 50-70 years old living in the community of south-eastern Poland. The respondents were divided into 2 study groups: group I - late middle age (50-60 years old) and group II - early old age (61-70 years old). With the use of questionnaires they were given, we obtained their socio-demographic data, assessed their cognitive and emotional state, as their physical activity levels. We used the Tinetti test to assess their gait and balance. Results We did not find statistically significant difference in cognitive functioning between the studied groups (p = 0.109). Moreover, there was no significant relationship between belonging to an age group and suffering from depression (p = 0.06) as well as no major differences were observed in the general level of physical activity in relation to age (p = 0.112). Our study found that most of our subjects, regardless of gender, declared their willingness to continue professional work after reaching retirement age. Conclusions The results of own research did not show significant differences in psychophysical state between people in late middle age and at the beginning of old age. Most of the researched participants declared their willingness to continue professional work. Due to changing demographic conditions, it is becoming an important issue to maintain the highest possible level of professional activity of older people in the labor market in Poland. Med Pr 2018;69(4):375-381